Letters to Lee: Mentoring the New Minister - Clayton, Paul C. (Rowman & Littlefield Publishers, 1999)
Each year, hundreds of newly ordained pastors enter their first congregations, unsure whether seminary training has truly prepared them for the day-to-day work of parish ministry. Clayton uses a unique epistolary format—from an older, experienced pastor to a novice—to address wisely such issues as preparing for weddings, funerals, and baptisms; planning education, evangelism, and stewardship programs; growing spiritually; developing a leadership style; and maintaining personal and professional boundaries. Highly acclaimed while used in Clayton’s Andover Newton seminary classes, this book is the perfect introduction to parish ministry for students, new pastors, and mentors.